Students' Perception on the Use of Kahoot as a Learning Media - Ana Rusmardiana; Dian Wardiana Sjuchro; Dewi Yanti; Fitri Daryanti; Akbar Iskandar (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study analyzes students' perceptions of Kahoot as a learning evaluation medium. This type of research is descriptive quantitative. The sample in this study was 68 grade 8 junior high school students. Data was collected through a questionnaire with the help of Google Form. Then the data is interpreted and analyzed to see the usefulness of Kahoot! in learning. The results showed that as many as 71.6% of students agreed that Kahoot increased student motivation in the good category; 91.7% of students agree that Kahoot improves learning effectiveness in the very good category; and 81.2% of students agree that Kahoot improves students' knowledge in the good category. Thus students' perceptions of learning motivation, learning effectiveness, and student knowledge can be increased with Kahoot. Therefore, it is recommended that teachers use Kahoot as an alternative media to help teachers evaluate learning